Pengaruh Media Diorama Berpendekatan Saintifik Terhadap Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - Utari, Winda Puji; Hetilaniar, Hetilaniar; Dirgantara, Marvinda Rizki Dita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to know determine whether diorama media with a scientific approachcan improve science learning outcomes for fifth grade elementary school students. This research is a type of quantitative research using the experimental method of True-Experimental Design research in the form of Posttest-Only Design. The variables of this study consisted of the independent variable (X) namely the diorama media and the dependent variable (Y) namely thelearning outcomes. The population in the study amounted to 75 students with 20 students asresearch subjects. Data collection techniques using tests and observations. Validation of the testinstrument was tested using the product moment correlation formula and the reliability test usingsplit-half. The data analysis technique used the T test, which was carried out after the normality andhomogeneity tests were known. The experimental class that was given treatment with diorama media obtained a posttest average of 79.50 and the control class obtained a posttest average of 61.00. The results of the t test with t table 2.024 obtained t count 4.349, it can be concluded that there is a significant influence on the use of scientific approach diorama media on science learning outcomes for fifth grade elementary school students.